2012
DOI: 10.1891/1946-6560.3.2.231
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Risk Factors for Intimate Partner Violence

Abstract: A systematic review of risk factors for intimate partner violence was conducted. Inclusion criteria included publication in a peer-reviewed journal, a representative community sample or a clinical sample with a control-group comparison, a response rate of at least 50%, use of a physical or sexual violence outcome measure, and control of confounding factors in the analyses. A total of 228 articles were included (170 articles with adult and 58 with adolescent samples). Organized by levels of a dynamic developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

150
1,518
15
57

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,527 publications
(1,740 citation statements)
references
References 189 publications
150
1,518
15
57
Order By: Relevance
“…Following the appropriate adjustments, it was found that participants reporting minor (PR = 1·23; 95 % CI 1·12, 1·35) and severe (PR = 1·16; 95 % CI 1·00, 1·34) reciprocal physical violence were more likely to be experiencing household food insecurity, compared with those not reporting physical violence. The potential confounding variables used in the analysis have been identified in several previous studies as associated with both intimate partner violence and food and nutrition insecurity (24)(25)(26) .…”
Section: Discussionmentioning
confidence: 99%
“…Following the appropriate adjustments, it was found that participants reporting minor (PR = 1·23; 95 % CI 1·12, 1·35) and severe (PR = 1·16; 95 % CI 1·00, 1·34) reciprocal physical violence were more likely to be experiencing household food insecurity, compared with those not reporting physical violence. The potential confounding variables used in the analysis have been identified in several previous studies as associated with both intimate partner violence and food and nutrition insecurity (24)(25)(26) .…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for IPV are complex, and encompass: demographic, family, gender, relationship, psychological, contextual and peer-related factors (Capaldi, Knoble, Shortt, & Kim, 2012). Similarly, HIV-related risk factors span a whole range, including: biological, social, behavioural, cultural, economic and structural (Ramjee & Daniels, 2013).…”
Section: Risk Factors and Health Consequences For Ipv And Hivmentioning
confidence: 99%
“…On the other hand, Capaldi et al [23] found evidence of a stronger association between drug use and IPV. A study by Caetano et al [24] found that alcohol did not predict male to female part-ner abuse.…”
Section: Discussionmentioning
confidence: 98%
“…In a systematic review by Capaldi et al, [23] the authors concluded that there is some evidence to support the positive association between alcohol use and intimate partner violence, but it was of a low magnitude and not found consistently. On the other hand, Capaldi et al [23] found evidence of a stronger association between drug use and IPV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation